Destabilized Calcium Hydride as a Promising High-Temperature Thermal Battery - Balakrishnan, Sruthy; Sofianos, M. Veronica; Paskevicius, Mark; Rowles, Matthew; Buckley, Craig (AMER CHEMICAL SOC, 2020)
Calcium hydride (CaH2) is considered an ideal candidate for thermochemical energy storage (thermal battery) due to its high energy density and low cost. Its very high operating temperature and poor cycling stability are the main factors that hinder its development and implementation as a thermal battery for concentrated solar power (CSP) plants. In this work, CaH2 was thermodynamically destabilized with aluminum oxide (Al2O3) at a 1:1 molar ratio to release hydrogen at a lower temperature than the hydride alone. Temperature-programmed desorption measurements showed that the addition of Al2O3 destabilized the reaction thermodynamics of hydrogen release from CaH2 by reducing the decomposition temperature to ∼600 °C in comparison to ∼1000 °C for pure CaH2 at 1 bar of H2 pressure. The experimental enthalpy and entropy of this system were determined by pressure composition isotherm measurements between 612 and 636 °C. The enthalpy was measured to be ΔHdes = 100 ± 2 kJ mol-1 of H2, and the entropy was measured to be ΔSdes = 110 ± 2 J·K-1 mol-1 of H2. The XRD after TPD and in situ XRD data confirmed the main product as Ca12Al14O33. The system exhibited a loss of capacity during hydrogen cycling at 636 °C, which was found to be due to sintering of excess Al2O3, as confirmed by X-ray diffraction and scanning electron microscopy. The hydrogen cycling capacity was significantly improved by reducing the initial amount of Al2O3 to a 2:1 molar ratio of CaH2 to Al2O3, deeming it as a highly promising high-temperature thermal battery for the next generation of CSP plants.